OUR EXPERIENCE IN USING MINIMALLY INVASIVE SURGICAL TREATMENT METHODS FOR FEMORAL FRACTURES - Ashirov M.U; Haydarov Samariddin Islom o'g'li; Isroilov Khushnudbek Erkin o'g'li; Sagdullayev Alibek Alisherovich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Fractures  of  the  trochanteric  region  of  the  femur  are  an  urgent  problem  of modern traumatology, which is associated with an increase in the number of patients with injuries to this localization. Given the severity of the general condition of patients, the  severity  of  osteoporosis  and  other  unfavorable  factors,  it  is  necessary  to  more widely introduce minimally invasive, low-traumatic methods for treating fractures of the trochanteric region of the femur in elderly and older patients. In 2023-2024, we performed  147  closed  percutaneous  osteosynthesis  operations  for  fractures  of  the trochanteric region of the femur, including 98 (66.6%) men, 49 (33.4%) women.